Numerical Approximation of the Maximum Power Consumption in DC-MGs with CPLs via an SDP Model (2019)
This brief addresses the numerical approximation of the maximum power consumption in direct-current microgrids (DC-MGs) with constant power loads through a convex optimizing model. The convex formulation is developed via a semidefinite programming model and is solved by using a MATLAB/CVX package. For comparison purposes the exact nonlinear model is solved in a GAMS package to compare the accuracy and quality of the results obtained with the proposed convex reformulation. Numerical testing is made with a small three-node DC-MG test system as well as DC-MGs from 10 to 150 nodes. © 2004-2012 IEEE.